Tumor microenvironment of metastasis and risk of distant metastasis of breast cancer - Rohan, Thomas E; Xue, Xiaonan; Lin, Hung-Mo; D'Alfonso, Timothy M; Ginter, Paula S; Oktay, Maja H; Robinson, Brian D; Ginsberg, Mindy; Gertler, Frank B; Glass, Andrew G; Sparano, Joseph A; Condeelis, John S; et al. (JNCI : Journal of the National Cancer Institute, 2014)
Tumor microenvironment of metastasis (TMEM), consisting of direct contact between a macrophage, an endothelial cell, and a tumor cell, has been associated with metastasis in both rodent mammary tumors and human breast cancer. We prospectively examined the association between TMEM score and risk of distant metastasis and compared risk associated with TMEM score with that associated with IHC4. We conducted a case-control study nested within a cohort of 3760 patients with invasive ductal breast carcinoma diagnosed between 1980 and 2000 and followed through 2010. Case patients were women who developed a subsequent distant metastasis; control subjects were matched (1:1) on age at and calendar year of primary diagnosis. TMEM was assessed by triple immunostain and IHC4 by standard methods; slides were read by pathologists blinded to outcome. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression, adjusted for clinical variables. A Receiver Operating Characteristic analysis was performed, and the area under the curve was estimated. All statistical tests were two-sided. TMEM score was associated with increased risk of distant metastasis in estrogen receptor (ER)(+)/human epidermal growth factor receptor (HER2)(-) tumors (multivariable OR high vs low tertile = 2.70; 95% CI = 1.39 to 5.26; P trend = .004), whereas IHC4 score had a borderline positive association (OR10 unit increase = 1.06; 95% CI = 1.00 to 1.13); the association for TMEM score persisted after adjustment for IHC4 score. The area under the curve for TMEM, adjusted for clinical variables, was 0.78. Neither TMEM score nor IHC4 score was independently associated with metastatic risk overall or in the triple negative or HER2(+) subgroups. TMEM score predicted risk of distant metastasis in ER(+)/HER2(-) breast cancer independently of IHC4 score and classical clinicopathologic features.